Underwater investigations standard practice manual - Childs, Kenneth M. (ASCE manuals and reports on engineering practice, 2001)
This manual provides guidance to the requestor and provider of underwater structural inspection services. Guidelines representing the standard of practice in the industry are presented for various inspection types, with the inspection types tailored to specific inspection objectives. The scope of work is defined for each inspection type, and guidelines are provided for the inspection of unique underwater structure types. References are provided for obtaining in-depth information on the structure types and defect types commonly found underwater.